Comparison of Conventional and Aerobic Iandfill Simulator Reactors (case study; Kirkuk city, Iraq) (Baghdad Science Journal, 2021)
Under aerobic and anaerobic conditions, two laboratory-scale reactors were operated. Each reactorwas packed with 8.5 kg of shredded synthetic solid waste (less than 5 cm) that was prepared according to anaverage composition of domestic solid waste in the city of Kirkuk. Using an air compressor, aerobicconditions were created in the aerobic reactor. This study shows that the aerobic reactor was more efficient inCOD and BOD5 removal which were 97.88% and 91.25% while in case of anaerobic reactor, they were66.53%and 19.11%, respectively.